Effectiveness of the Local Natural Methods of Extending Fruit Shelf Life in Selected Cooler Parts of Uganda. - Mwesigye, Deus (Kabale University, 2024)
Understanding agents that spoil avocado fruits enables us to develop ways of extending their shelf life which is key for storage and extended shelf life. Designing natural environmentally friendly techniques like treatment with conc. NaCl and applying aloe vera gel on the surface of avocados in a safer and health-conscious manner is paramount. Avocados are prone to postharvest deterioration caused by mechanical damage, rodent insect attack, and microbial activity. The avocado of the ‘Hass’ variety continues to be commercially grown worldwide and was used for this study on postharvest decay and disorders affecting fruit quality during storage. The study, conducted in Kabale Municipality, Kabale district in southwestern Uganda, investigated causes of spoilage, and natural and simple preservative methods that would extend shelf life. The results of the study found that microbial activity accounted for 61.7% of spoilage, Mechanical damage 22.7% while insects and rodents accounted for 15.6%. The fruits that were not preserved showed spoilage levels within the first two weeks (p = 0.011); those preserved by Conc. NaCl solution had the level of spoilage in the third week (p= 0.004); while preservation level was significant in the third and fourth weeks at (p = 0.002 and p = 0.056) respectively but more significant in the third week. Mechanical injuries rupture the epicarp providing direct entries for microbes during storage. Poor physical handling and squeezing of individual fruit during selection by consumers also contribute to mechanical defects. More damage is apparent when avocados are just dropped down carelessly causing epicarp bruises. Avocado fruit shelf life is highly limited by fungi and bacterial infections. Many types of microorganisms can be found on fruit including Gram-negative bacteria, Gram-positive bacteria, and fungi (yeasts and molds). These fungal diseases account for perhaps over 60% of loss for this study related to the 70% of all fruit losses in other studies. The postharvest insect and rodent infestation also significantly affects the economic losses by causing physical damage as they feed or transmit the microorganisms. Treating the surface of the fruit with conc. NaCl solution kills the microorganisms and as well as reduces their further entry so is Aloe vera gel one of the natural compounds that has gained great interest. By addressing post-harvest losses, enhancing food security, and increasing farmers' incomes, these practices play a crucial role in improving the overall well-being of communities in such regions.